Aplicación de la computación afectiva en el análisis de la percepción de los asistentes a una feria de emprendimiento del SENA - Chanchí-Golondrino, Gabriel-Elias; Hernández-Londoño, Claudia-Estella; Ospina-Alarcón, Manuel-Alejandro (Revista Científica, 2022)
Affective computing is an emerging area of research that is focused on the development of systems with the ability to recognize, process, and simulate human emotions with the purpose of improving the interaction between the user and the system. One of the potential fields in which it can be used is marketing, through the study of user perception via the use of sentiment and emotion analysis techniques on the opinions of users with respect to the products and services offered by companies. As a contribution, this article proposes the development of a study on emotion analysis based on the text containing the opinions of the attendees to a virtual entrepreneurship fair called Marketing from Home, which was developed during the pandemic lockdown and co-organized by SENA and Universidad de Cartagena. To carry out this research, four methodological phases were taken into account: exploration and selection of technologies for emotion analysis; cleaning and adapting the text of the opinions; obtaining the percentage distribution of emotions in the text with the opinions; and analyzing the perception of the fair attendees. The study allowed determining the percentage distribution of the six basic emotions (happiness, anger, sadness, euphoria, fear, and boredom) across the text containing the opinions of the attendees to the Marketing from Home virtual fair, in order to obtain the general perception of the logistics, the virtual stands, and the products offered.